Experimental and theoretical study of spectroscopy of binuclear difluoroborate dipyrromethene complexes - Aksenova, Yulia V.; Pomogaev, Vladimir A.; Kuznetsova, Rimma T.; Antina, Lubov A.; Berezin, Michail B. (Russian physics journal)
The spectroscopic characteristics of mono and binuclear difluoroborate complexes of dipyrromethenes in various solvents and solid-state polymer media (films) are investigated depending on the wavelength and intensity of the exciting radiation. Along with experimental studies, quantum-chemical calculations of the electronic structure and geometry of electronically excited molecules were carried out, an interpretation of the experimental data (absorption and emission bands) was given, and a connection between the absorption spectra and the structure of bis(dipyrromethenes) and their conformations was established. The analysis of the obtained results is carried out in comparison with the modern literature data. The possibilities of practical application of the studied compounds in the development of liquid and solid-state lasers and optical solvent polarity sensors are discussed.